Supply Chain Strategies in Russia’s Special Administrative Regions: Does It Recover the National Economy? - Viacheslav A. Andreev; Tat’ayna V. Varkulevich; Marina N. Arnaut; Lev S. Stavnichiy (International Journal of Supply Chain Management, 2020)
Abstract-Due to the economic sanction the Russian Federation has taken a vigorous attempt to compensate the risk for the national economy stipulated by restriction with access to the capital markets and supply chain strategy by constraints to compete in international markets. Imposition of the special administrative regions is a respond to the sanctions by the United States and a few countries in order to minimize possible financial losses. In an uncertain recovery, supply chain operations need to be more scalable and flexible as they anticipate economic recovery and increase capacity.In practice, a special administrative area appears as offshore financial center. However, its goal is broader – to ensure the repatriation of capital withdrawn off the Russian jurisdiction in 1998-2018. The aim of study is to estimate the capital which will prospectively be returning to Russia until 2025 through the special administrative regimes at Russkiy island and Oktyabr’skiy island in the Russian Federation. The findings show that the capital flight off the Russian economy has amounted to 653.2 billion US dollars for the last 20 years. But viewing the result of sanction’s pressure, by 2025, the total return of capital from the offshores at Cyprus and the Virgin Islands could prognostically reach 165.55 billion dollars. Special administrative region’s preferences will motivate large foreign holdings, especially those that have fallen under sanctions, to change their registration to the Russia’s domicile. Therefore, the special administrative regions could prospectively facilitate investment inflow and stipulate recovering the Russia’s economy.